Yield and nitrogen use efficiency of lowland rice genotypes as influenced by nitrogen fertilization - Fageria, Nand Kumar; Santos, Alberto Baêta dos; Cutrim, Veridiano dos Anjos (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the yield of lowland rice genotypes as affected by nitrogen fertilization. A field experiment was conducted, during two consecutive years, in order to evaluate the response of 12 irrigated rice genotypes to five doses of N application. The N doses used were 0, 50, 100, 150 and 200 kg ha-1. Genotypes differed significantly in relation to grain yield. Response of genotypes to N rate was significant and quadratic. Genotypes BRSGO Guará and BRS Alvorada had maximum grain yield and BRS Jaburu and BRS Biguá were the lowest yield producers, during two years of cultivation. Higher productivity of BRSGO Guará and BRS Alvorada was associated with higher panicle number, higher grain harvest index, and low grain sterility at higher N rates. Genotypes also differed in N use efficiency regarding grain produced per kilogram of N applied, and regarding N accumulated in the plant or recovered by plant.